Hypoxia-Induced GST1 Exerts Protective Effects on Trophoblasts via Inhibiting Reactive Oxygen Species (ROS) Accumulation - Lingjuan Chen; Gaoli Chen; Lixuan Guo; Yaping Wang; Chengjin Ai (Analytical Cellular Pathology)
Hypoxic conditions are a typical extrinsic factor for the modification of trophoblast biological functions, including cell proliferation, migration, and invasion. Hypoxia-induced reactive oxygen species (ROS) accumulation causes chronic trophoblast injury and contributes to preeclampsia (PE). Glutathione-S-transferase P (GSTP1) is a main regulator of ROS. However, it is still unknown whether GSTP1 is involved in ROS regulation under hypoxic conditions. Here, we investigated the expression level of GSTP1 in first-trimester villi placentas compared with full-term placentas and the effect of hypoxic conditions on GSTP1. GSTP1 expression in first-trimester villi placentas was much higher than that in full-term placentas. After hypoxia exposure, GSTP1 was significantly upregulated in JEG3 cells, a trophoblast-like cell line. Hypoxic-induced GSTP1 scavenged ROS accumulated by hypoxia exposure, potentially by promoting GST activity. The inhibitory effects of hypoxia exposure on cell proliferation, migration, and invasion induced by hypoxia exposure were obviously reversed by overexpression of GSTP1. Hypoxia-induced cell apoptosis was also reversed by GSTP1 overexpression, indicating the protective effects of GSTP1 against ROS-induced cell injury. Moreover, overexpressed GSTP1 markedly promoted the cell proliferation, migration, invasion, and colony formation abilities in JEG3 cells, demonstrating that GSP1 also exerts promoting effects under normoxic conditions. These data show that hypoxia-induced GSTP1 expression facilitates trophoblast cell proliferation, migration, and invasion and exerts protective effects under hypoxic conditions, which may play an important role during the increase in PE.